The burden and characteristics of tuberculosis/human immunodeficiency virus (TB/HIV) in South Korea: a study from a population database and a survey - Kim Hee-Jin; Do Heonsook; Kim Jinhyun; An Jung-wook; Oh Eunjung; Kee Mee-Kyung; Oh Dae-Kyu; Hwang Ji-young; Lee Chang-Hoon; Kim Sung; Kim Hwahyun; Nam Jeong-Gu (BMC Infectious Diseases, 2010)
Abstract Background Although, in South Korea, human immunodeficiency virus/acquired immunodeficiency syndrome(HIV/AIDS) keeps increasing and tuberculosis(TB) burden is still significant, there have been few reports on TB/HIV cases. In this study, we investigated the burden and characteristics of TB/HIV patients in South Korea, an area with intermediate burden of TB and a low prevalent area with HIV/AIDS. Methods We identified patients with TB and cases with HIV between January 1 2001 and December 31 2005, from nationwide reporting system (TBnet and HIV/AIDS registry) through an electronic record linkage method. A questionnaire survey was also conducted and determined the rate of diagnosis of HIV among TB cases in public health units in 2005. Results The number of cases with both HIV and TB was 137 (0.07% among 197,562 TB cases) and the newly detected TB/HIV cases per 100,000 population was increasing annually: 2001, 0.025; 2002, 0.031; 2003, 0.025; 2004, 0.071; 2005, 0.095. Males between 20 and 59 years of age accounted for 87.6% of TB/HIV patients. Compared with patients with TB alone, those with TB/HIV had a higher percentage of extrapulmonary TB (8.0% vs 19.0%; p < 0.0001). The standardized prevalence ratio (SPR) of HIV among patients with TB was 18.46 (95% CI, 15.50-21.83). SPR of HIV among male TB patients aged 20-59 and extrapulmonary TB cases was 39.64 (95% CI, 32.87-47.40) and 43.21 (95% CI, 28.22-63.31) respectively. Through a questionnaire survey of public health units, six patients (0.08%) were confirmed as having HIV among 7,871 TB patients in public health centers in 2005, which is similar to the result from the study through nationwide reporting systems. Conclusions The prevalence rate of TB/HIV patients is still low but increasing in South Korea. Physicians should consider performing HIV tests among TB patients, especially in higher-risk groups, such as young males with extrapulmonary TB in South Korea.